Noninvasive Tests Accurately Identify Advanced Fibrosis due to NASH: Baseline Data From the STELLAR Trials. Issue 5 (19th August 2019) - Anstee, Quentin M.; Lawitz, Eric J.; Alkhouri, Naim; Wong, Vincent Wai‐Sun; Romero‐Gomez, Manuel; Okanoue, Takeshi; Trauner, Michael; Kersey, Kathryn; Li, Georgia; Han, Ling; Jia, Catherine; Wang, Lulu; et al.
Abstract : Accurate noninvasive tests (NITs) are needed to replace liver biopsy for identifying advanced fibrosis caused by nonalcoholic steatohepatitis (NASH). We analyzed screening data from two phase 3 trials of selonsertib to assess the ability of NITs to discriminate advanced fibrosis. Centrally read biopsies from the STELLAR studies, which enrolled patients with bridging fibrosis and compensated cirrhosis, were staged according to the NASH Clinical Research Network classification. We explored associations between fibrosis stage and NITs, including the nonalcoholic fatty liver disease fibrosis score (NFS), fibrosis‐4 (FIB‐4) index, Enhanced Liver Fibrosis (ELF) test, and liver stiffness by vibration‐controlled transient elastography (LS by VCTE). The performance of these tests to discriminate advanced fibrosis, either alone or in combinations, was evaluated using areas under the receiver operating characteristic curve (AUROCs) with 5‐fold cross‐validation repeated 100 times. Of the 4, 404 patients screened for these trials, 3, 202 had evaluable biopsy data: 940 with F0‐F2 fibrosis and 2, 262 with F3‐F4 fibrosis. Significant differences between median values of NITs for patients with F0‐F2 versus F3‐F4 fibrosis were observed: −0.972 versus 0.318 for NFS, 1.18 versus 2.20 for FIB‐4, 9.22 versus 10.39 for ELF, and 8.8 versus 16.5 kPa for LS by VCTE (all P  < 0.001). AUROCs ranged from 0.75 to 0.80 to discriminate advanced fibrosis. FIB‐4 followed by an LS by VCTE or ELF test in those with indeterminate values (FIB‐4 between 1.3 and 2.67) maintained an acceptable performance while reducing the rate of indeterminate results. Conclusion: Among patients being considered for enrollment into clinical trials, NITs alone or in combination can reduce the need for liver biopsy to discriminate advanced fibrosis caused by NASH. The predictive value of these tests for general screening will require confirmation in a real‐world population.